NEGOSIASI, IDEOLOGI, DAN BATAS KESARJANAAN - Rohmana, Jajang A (Lajnah Pentashihan Mushaf Al-Qur'an, 2019)
This study discusses the translatorâ€™s experience in the project of Sundanese translation of the Qurâ€™?n being published by the Agency of Research, Development, Education and Training of Ministry of Religious Affairs of Republic of Indonesia in 2018-2019. The project was organized by Sundanese scholars of the State Islamic University of â€œSunan Gunung Djatiâ€ and Padjadjaran University, Bandung. As one of the translator team members, the writer tried to phenomenologically explain the language negotiations, the ideology of the majority in Qurâ€™anic translation and the limit of academic behind the project. The result of the study shows that the project of Qurâ€™anic translation which is funded by Indonesian government involved not only academic problems, but also non-academic ones. It is not only related to the discussion of the substance of the Qurâ€™anic translation which became the medium of negotiations between the expert of the Qurâ€™?n and the Sundanese language, but also involved the administration and government control to the ideology of Islamic majority. This study also shows that the academic has to be neutral and objective in order to able to transcend the ethnic and ideological boundaries. This article is part of the writerâ€™s argument based on the writerâ€™s choice, although as part of the translator team, he has been overshadowed by the ideology of Islamic majority.